1986
DOI: 10.1071/ea9860539
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of teat number and its relationship to production characters in male pigs

Abstract: Heritability of teat number and its correlation with the production characters, growth rate, feed conversion ratio and backfat depth, were examined. Data were obtained from 456 Large White, 1370 and race and 78 Synthetic boars submitted to the Queensland boar performance testing station.Teat number (mean � s.e.) of Large White boars was 14.44 � 0.05, significantly ( P < 0.05) more than either Landrace (14.27 � 0.03) or Synthetic boars (14.10 �0.12). The heritability estimate (� s.e.) for teat number of boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In our experiment each F 2 -animal had two fullsibs as parents and therefore, if effects of recessive alleles reducing teat number exist, they would become apparent here. An average teat number of 14.1 in the F 1 and 13.8 in the F 2 in crosses involving Piétrain, Landrace and Large White pigs is concordant with the reported average teat number for these breeds in the literature (ALLEN et al, 1959;SKJERVOLD, 1963;HANSET and CAMERLYNCK, 1974;SMITH et al, 1986;ORZECHOWSKA and MUCHA, 1998). The observed phenotypic variation is in good agreement with NACHTSHEIM (1925) who stated that teat number ranges from eight to 18 and that 14 teats are the normal number.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In our experiment each F 2 -animal had two fullsibs as parents and therefore, if effects of recessive alleles reducing teat number exist, they would become apparent here. An average teat number of 14.1 in the F 1 and 13.8 in the F 2 in crosses involving Piétrain, Landrace and Large White pigs is concordant with the reported average teat number for these breeds in the literature (ALLEN et al, 1959;SKJERVOLD, 1963;HANSET and CAMERLYNCK, 1974;SMITH et al, 1986;ORZECHOWSKA and MUCHA, 1998). The observed phenotypic variation is in good agreement with NACHTSHEIM (1925) who stated that teat number ranges from eight to 18 and that 14 teats are the normal number.…”
supporting
confidence: 86%
“…It was found by LIU et al (1995) that the defect of inverted teats in the Shanxi Black breed is due to a single autosomal recessive gene. Allen et al, 1959Enfield and Rempel, 1961Skjervold, 1963Willham and Whatley, 1963Hanset and Camerlynck, 1974Pumfrey et al, 1980Clayton et al, 1981Smith et al, 1986 McKay and Rahnefeld, 1990Kuciel and Chvatalova, 1992Gaur and Chhabra, 1995Ligonesche et al, 1995Seo et al, 1996Wang et al, 2000Zhang et al, 2000Lee and Wang, 2001Hirooka et al, 2002 154 3565 2180 1362 1473 18704 4342 1579 7513 2148 3202 456 1370 78 5351 4711 4033 1083 3803 2134 2130 2504 1464 1848 1894 2802 18632 19109 13454 59 .10 -.23 .22 -.28 .16 -.30 .29 -.36 .28 -.40 .46 .34 .32 -.44 .07 -.48 .20 .23 .32 .20 .39 .44 .45 .43 .27 .47 .32 -.53 .35 -. 42 .15 .25 .25 .07 -.09 .66 .43 -.53 .54 -.79 .53 Recently, first studies showed evidence for quantitative trait loci (QTL) on Sus scrofa chromosomes 1, 2, 3, 6, 7, 8, 10, 11, 12 and 16 (WADA et al, 2000;BIDANEL et al, 2...…”
Section: Introduction Teat Numbermentioning
confidence: 99%